Ion Conducting Behavior of Silsesquioxane-Based Materials Used in Fuel Cell and Rechargeable Battery Applications - (:unkn) unknown (PLEIADES PUBLISHING INC, 2018)
The worldwide energy demand is expected to be double of the current consumption in the near future. This huge energy demand increases the importance of energy conversion and storage devices. A fuel cell needs an electrolyte which can be used under high temperature conditions for increasing the system efficiency. In the case of rechargeable batteries, the ion-conducting properties of the electrolyte should possess long-term sustainability. However, available electrolytes for a fuel cell can efficiently work only at temperatures below 100 degrees C. On the other hand, commercially used electrolytes are usually liquids and may cause serious leakage and safety problems, thus their sustainability is limited for Li-ion battery applications. Although their ionic conductivities are relatively low, solid and gel type electrolytes are safer and therefore become more favorable. More recently, compatible hybrid organic-inorganic polyhedral oligomeric silsesquioxane (POSS) derivatives have attracted much attention of researchers in order to obtain solid or gel type electrolytes. These materials combine the intrinsic mechanical and thermal properties owing to the inorganic core and the compatibility owing to the organic coronae. Therefore POSS derivatives are a promising family that can allow the design of alternative energetic materials. Here, the objective is to increase the awareness of the role of POSS-based materials for fuel cell and rechargeable battery applications.
Keywords: silsesquioxane; electrolyte; fuel cell; Li-ion battery; POLY(ETHER ETHER KETONE); COMPOSITE MEMBRANES; POLYHEDRAL OLIGOSILSESQUIOXANE; POLYMER ELECTROLYTES; HYBRID MEMBRANES; POSS; NANOCOMPOSITES; CHALLENGES; POLYIMIDE; STABILITY